Temperature-Dependent Cluster Decay Half-Lives - Rojas-Gamboa , D. F. (2023)
Temperature-dependent cluster decay half-lives are investigated based on the double folding model (DFM). The temperature dependence of the interaction potential is introduced through the charge and matter density distributions of the interacting nuclei, and the half-lives are calculated within a preformed cluster model. Subsequently, the temperature-dependent universal decay law (UDL) is fitted using the half-lives calculated with the double folding model.